pH and reduction dual-responsive micelles based on novel polyurethanes with detachable poly(2-ethyl-2-oxazoline) shell for controlled release of doxorubicin - Leran Bu; Hena Zhang; Kang Xu; Baixiang Du; Caihong Zhu; Yuling Li (Taylor & Francis Group, 2019)
We describe a biodegradable amphiphilic polyurethane (PU) with disulfide bonds in the main chain [PEtOz-b-PU(SS)-b-PEtOz]. This multi-block PU was synthesized using poly (ε-caprolactone) diol (PCL-SS-PCL) and poly (2-ethyl-2-oxazoline) (PEtOz-OH) as soft segments, and bis (2-isocyanatoethyl) disulfide as the hard segment. Acid-sensitive PEtOz-OH was used as a hydrophilic segment for pH sensitivity. And reduction sensitivity was induced via disulfide bonds incorporated into the hydrophobic poly (ε-caprolactone) segment of the amphiphilic PUs. The system can self-assemble to form micelles responsive to pH and reducing conditions. The properties of the micelle were studied with dynamic light scattering and scanning electron microscopy. Doxorubicin (DOX) was chosen as a model drug. The in vitro release studies showed that PEtOz-b-PU(SS)-b-PEtOz micelle could degrade more rapidly and completely in a reductive and acidic environment [10 mM dl-Dithiothreitol, pH 5.0]. The methyl tetrazolium (MTT) assay and fluorescent microscopy confirmed the cytotoxicity of the DOX-loaded micelles. This work provides a promising dual-responsive drug carrier based on amphiphilic PU to achieve efficient drug delivery.